A preliminary study on the bacteriological quality of untreated well water from tawang and Pengkalan Chepa, Kelantan - Yahaya, Norihan (Universiti Sains Malaysia, 2015)
In Kelantan, an average 69.3% of its population is still depending on the untreated groundwater for drinking and other uses. Untreated groundwater has shown to bring illhealth effects to humans. The aim of the study was to determine the bacteriological quality of untreated well water from the district of Tawang and Pengkalan Chepa. Ninety (90) samples from thirty (30) sampling points were randomly selected from December 2014 until February 2015. Water samples were analysed using the membrane filtration method. The results showed the E. coli count is within the acceptable level (1-10 cfu/100ml). Pengkalan Chepa relatively has an excellent well water quality compared to Tawang. The number of samples that categorised as an acceptable criteria for drinking water at Tawang and Pengkalan Chepa was about 14 (93.33%) and 15 (100%) of 15 samples respectively. Only 1 sample contain E. coli in the range of 10-50 colony counts at Tawang that indicates that water was unacceptable to be used as drinking. Water samples from both study locations are far from grossly polluted and can be used as a safe source of drinking water.